Implementasi Aplikasi Pengolahan Nilai Berbasis Web Untuk Meningkatkan Kinerja Guru Dalam Proses Belajar Mengajar di Sekolah - Sefrika Entas (Universitas Bina Sarana Informatika, 2017)
Education is the spearhead of the nation's progress. To improve the quality and quality of education can be done in various ways that improve the quality of teaching staff and other supporting resources. One of the supporting methods of improving the quality of education in Indonesia is the use of information technology. The problem that occurs today is the use of information technology is very minimal. The processing of academic data, teaching and learning activities to the preparation of academic results report is still done manually so it has a big risk to data errors. Therefore we need an application that can help facilitate the process of teaching and learning, academic data management, and reporting of educational results to parents who can be accessed in real time. This research uses waterfall software development method, discuss PHP programming and MySQL database. The results of research in the form of academic value processing applications can be used to improve teacher performance and improve the quality of education in Indonesia.